pengaruh FAKTOR KOMPETENSI, INDEPENDENSI, DAN SIKAP PROFESIONAL TERHADAP KUALITAS AUDIT PADA INSPEKTORAT PROVINSI KALIMANTAN TIMUR - Taufik Rama Dani; Lewi Malisan; Ferry Diyanti (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
TAUFIK RAMA DANI. Effect factors of competence, independence, and professional attitude of theauditor on quality of audit at inspectorate province east borneo. Under guidance of Mr. Lewi Malisanand Mrs. Ferry Diyanti.Based on the background that you have described, then the formulation used is whether competence,independence, and professional attitude of the auditor to audit quality. The purpose of this research isto know the influence of competence, independence, and professional attitude of the auditor's audit onthe quality produced by the Apparatus Inspectorate of East Kalimantan province. The benefits of thisresearch is done is to supplement science knowladge on factors effect the quality of audits.The theory of attribution used to know things that affect one's actions. The theory of attitude andbehavior was seen as the underlying theory to explain the independence and professional attitude, thetheory States that the person's behavior is determined by what the people want to do(attitude), whatthey think will do (social rules) and what to do (habits).The development of a hypothesis made is competence, independence, and professional attitudepositive effect to the quality of audits. Data collection through qualitative methods. Qualitative withthe dissemination of a questionnaire on customers and employees.The population in this research is the entire Apparatus of the civil State (ASN) at the Inspectorate ofEast Kalimantan province. The sample in this study was 35 employees of the Inspectorate have thecertification Office of the Auditor Fungiosnal (JFA).From the results of the analysis using the program SMARTPLS V. 2 research results for hypothesistesting showed that competence, independence, and professional attitude is positive and significantinfluential Auditors of the quality audit Inspectorate of East Kalimantan province.Key word : Competence, Independence, and Professional attitude, Quality of audit